2019
DOI: 10.3389/fimmu.2019.01286
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Characteristics and Poor Prognostic Predictors in Patients With an Initial Diagnosis of Autoimmune Encephalitis

Abstract: Purpose: We aimed to retrospectively analyze the clinical features, laboratory and imaging results, and predictors of poor prognosis for patients with an initial diagnosis of autoimmune encephalitis (AE) at the Affiliated Hospital of Zunyi Medical University. Methods: Fifty patients with an initial diagnosis of AE who were admitted to our hospital from May 2014 to May 2018 were enrolled retrospectively. Clinical characteristics and experimental test data, including the neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 54 publications
(68 reference statements)
5
38
1
Order By: Relevance
“…The optimal cut-off to predict severe disability (mRS >2) was an NLR >4.82 (AUC 0.875). A subsequent study examined a group of 50 AE cases and their long-term functional outcomes ( 10 ). The investigators found that after a median of 11 months follow-up, the NLR on admission was associated with higher odds of mRS >1 (OR 2.17, 95% CI 1.03–4.57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal cut-off to predict severe disability (mRS >2) was an NLR >4.82 (AUC 0.875). A subsequent study examined a group of 50 AE cases and their long-term functional outcomes ( 10 ). The investigators found that after a median of 11 months follow-up, the NLR on admission was associated with higher odds of mRS >1 (OR 2.17, 95% CI 1.03–4.57).…”
Section: Discussionmentioning
confidence: 99%
“…We recorded the total white blood cell count and immune cell subset counts from the first full blood analysis within 24 h of admission ( 10 ). We excluded any patient who had confounding illness that with potential impact on white blood cell counts such as systemic infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be relevant because complement activation on autologous cells are tightly controlled and mostly stop after the deposition of C4b. We postulate that C4B deficiency in our patient might have led to the defective removal of immune complexes and possibly impairment of yet to be characterized neurogenic pathways, which has a substantial role in autoimmune encephalitis [9][10][11]. Complement deficiency is ameliorated by plasmapheresis, which normally correct the complement deficiency, but not by IVIG.…”
Section: Discussionmentioning
confidence: 83%
“…Multiple autoimmune encephalitis, either seropositive or negative, show different types of unspecific EEG alterations such as: frontal intermittent rhythmic delta activity (FIRDA), periodic lateralized epileptiform discharge (PLED), periodic epileptiform discharges (PED), generalized rhythmic delta activity (GRDA), excess beta activity (EBA) and triphasic waves [14][15][16][17][18]. An example is showed in Figure 4.…”
Section: Eeg In Encephalitismentioning
confidence: 99%